ANALISIS PENGELOLAAN KEUANGAN DI SMP LABSCHOOL UNESA 2 DALAM MENDUKUNG KEGIATAN PENDIDIKAN - Rifi Al Arifin; Azizah lailatus Syifa; Evania sari; Shafira Rahmadini; Elsya Amelia Putri; Ima Widiyanah (STKIP Subang, 2026)
This study aims to analyze the financial management of SMP Labschool UNESA 2 in supporting educational activities, encompassing the stages of planning, organizing, implementation, as well as supervision and evaluation. This research employs a qualitative descriptive approach with data collected through in-depth semi-structured interviews with the school principal, school treasurer, and BOS treasurer, as well as documentation studies. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana (2014), with validity ensured through source and technique triangulation. The results indicate that financial planning is based on Dapodik data and the school's educational report card; organizing is carried out through a clear division of responsibilities supported by the ARKAS application; implementation is conducted in accordance with applicable regulations using ARKAS and SIPLAH systems; and supervision is performed through periodic document verification and reporting to the Education Office via SIPKS. Overall, financial management at SMP Labschool UNESA 2 has been implemented in accordance with the principles of transparency, accountability, effectiveness, and efficiency in supporting the quality of educational activities.